Analisis Hukum terhadap Akta Jual Beli Tanah yang Tidak Didaftarkan ke Badan Pertanahan Nasional - Mandigani, Adisa Indira (Faculty of Law Universitas Islam Indonesia, 2024)
Land is a strategically valuable asset in Indonesian society, both socially, economically, and legally. One of the most common forms of land transfer is through sale and purchase. Although the Basic Agrarian Law and Government Regulation No. 24 of 1997 require registration of every transfer of rights to be legally valid, in practice, many sales and purchase transactions only proceed with the issuance of a Deed of Sale and Purchase (AJB) by the Land Deed Official (PPAT), without further registration with the National Land Agency (BPN). This situation raises serious legal issues, because without registration, land rights are not legally transferred and buyers do not receive adequate protection. The problem formulation in this study is the legal status of land sale and purchase deeds that are not registered with the BPN and what are the legal consequences for the parties of such unregistered land sale and purchase deeds. The study uses a normative juridical method through a review of laws and regulations, legal doctrine, and other related provisions. The results show that unregistered AJBs do not have constitutive force in the Indonesian land law system. Buyers lose legal protection and are vulnerable to disputes, and cannot legally transfer, inherit, or pledge the land. Therefore, the title registration system places registration as a prerequisite for legal transfer of rights. Therefore, strengthening regulations, oversight, and education is necessary to raise awareness of the importance of registration in every land transaction.